Assessment of genetic variation in selected germplasm of white jute (Corchorus capsularis L.) - Alam, M. J.; Pramanik, Md. Enayet Ali; Ferdous, Jannatul; Islam, Md. Monirul (Universiti Putra Malaysia Press, 2016)
Fifty-one genotypes of white jute from different geographic origins were evaluated to study their genetic variability with 11 morphological characters. Significant variation was observed among the genotypes for all the characters. Multivariate techniques were used to classify 51 genotypes. All the genotypes were grouped into six different clusters. Principal component analysis, principal coordinate analysis and canonical vector analysis gave similar results to that of cluster analysis. The highest inter-genotypic distance (1.84) was found between G15, G50 and the lowest distance between G38 and G26. The highest inter-cluster distance (14.37) was observed between cluster I, IV and the lowest distance (2.46) was between cluster III and V. The highest intra-cluster distance was found in cluster I and lowest in cluster V. Considering genetic parameters, high genotypic coefficient of variation (GCV) was observed in branches per plant. High heritability values with moderate genetic advance in percentage of mean were obtained for leaf width, petiole length, nodes per plant. Regarding the cluster distance, inter-genotypic distance and other agronomic performance, the genotypes G47, G33, G48 from cluster I; G27, G17, G23 from cluster III and G13, G40, G45 from cluster II were considered to be better parents for future use in hybridisation programmes.